Disclosure socioambiental de empresas abertas: 40 anos depois, as mesmas lacunas de antes? - Campanholo, Thalita Pereira Caetano (2019)
This research aimed at verifying the historical behavior and frequency of disclosures about the corporate social responsibility of Brazilian companies that compose the IBrX-50 index from 2000 to 2018. To this end, we analyzed the annual management reports that these companies provided to the market from the perspective of 31 items according to the study by Walter and Monsen (1979) on corporate social responsibility, with environment, equal opportunities, personnel, involvement with the society, products, others, and location of the disclosure. An analysis was performed with primary data collection in the records and were used based on the previous items. The study sample consisted of 47 companies listed in B3 that are part of the IBrX-50 index. Measurement of the disclosure level became possible with the content analysis of the selected reports in the light of the 7 topics mentioned, as well as the use of regression analysis to associate the variables year, sector, revenue, indebtedness, profitability, and ISE with the disclosure of CSR. The results show that while the average of CSR disclosures in management reports was 48.5% during 2000-2008, in 2010 there were decreases of 3% and an increase of 2% in 2012. These results critically suggest that elements already pointed out in the literature in the 1970s (based on the study by Walter and Monsen, 1979), even after 40 years, may still be aspects that require greater attention in corporate reporting. It found that although the year, profitability, indebtedness and sector have no significant influence on the disclosure of CSR, on the other hand, the revenue and the fact that being part of the ISE has positive associations. It can be concluded that the disclosure of CSR is a way of becoming aware of what corporations have been performing in terms of social and environmental aspects in society. Besides, this subject can also bring benefits to the corporate image and trust of the parties. It is expected that the study will contribute and instigate discussions about CSR disclosure and its evolution over the last 10 years, and present the relationships with entities' economic variables.